Detección de Parásitos Intestinales Humanos en Vectores Mecánicos. San Andrés, 2019 - Shirley Paola Echeverría Núñez (2019)
Parasitic infections are a global problem, producing various chronic or acute gastrointestinal diseases; several risk factors help human parasites spread. This researching is of mixed qualitative-quantitative approach, with a cross-sectional, exploratory, and non-experimental research; whose objective was to identify human intestinal parasites in mechanical-biological vectors. It is detennining them as a transmission risk factor, through the use of techniques such as direct observation, through instruments such asthe observation sheet, field diary, and camera. The population studied was the comrnunity of San Andrés belonging to the Guano canton where common houseflies and so1ne arthropods found in different strategic locations are taking as a sample. The arthropods were caught by manual capture technique with a plastic sheath being the most appropriate because thanks to this, it was possible to catch large numbers of insects. In the processing, it was possible to find a variety of parasites such as Entamoeba coli, Entamoeba histolytica / E. disparate, different morphological stages of Blastocystis spp, Cyclosporas, Cystoisospora, Giardia intestinalis cysts, Iodamoeba butschlii, helminth eggs. They are thus determining that mechanical-biological vectors are a significant risk factor for transmission of human intestinal parasites.